The strategy guidance of business English intercultural communication based on blockchain security and genetic algorithms. Issue 2 (23rd February 2022) - Zhang, Baicheng
Abstract: With more and more frequent exchanges between countries, English as an international language has received more attention, especially the concept of "global village" proposed in recent years, which has narrowed the distance between countries. As a communication tool, business English is often used in cross‐cultural communication, and this article aims to analyze the misuse of business English in cross‐cultural communication. This paper proposes a language error analysis system based on blockchain security technology, which is based on blockchain security technology, which can well guarantee the security in business communication. It also proposes an optimization strategy based on genetic algorithm, which greatly improves the effect and efficiency of the system. The experimental results show that the system can more accurately detect language errors in business English communication. In the 22 scenes surveyed, only 3 scenes have mistakes, and in the scenes of mistakes, the accuracy rate can reach more than 90%. This shows that the system can provide support for cross‐cultural communication in business English, and can accurately and efficiently complete business English language errors.